2019
DOI: 10.1063/1.5097821
|View full text |Cite
|
Sign up to set email alerts
|

Faber polynomial coefficient estimates for a class of analytic bi-univalent functions

Abstract: In the present paper, we were mainly concerned with obtaining estimates for the general Taylor-Maclaurin coefficients for functions in a certain general subclass of analytic bi-univalent functions. For this purpose, we used the Faber polynomial expansions. Several connections to some of the earlier known results are also pointed out.2010 Mathematics Subject Classification. 30C45.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A function f ∈ A is said to be in Σ the class of bi-univalent in U if both f (z) and f −1 (z) are univalent in U. Lewin [9] showed that |a 2 | < 1.51 for every function f ∈ Σ given by (1.1). Posteriorly, Brannan and Clunie [3] improved Lewin's result and conjectured that |a 2 | ≤ √ 2 for every function f ∈ Σ given by (1.1). The coefficient estimate problem for each of the following Taylor Maclaurin coefficients:…”
Section: Introductionmentioning
confidence: 93%
“…A function f ∈ A is said to be in Σ the class of bi-univalent in U if both f (z) and f −1 (z) are univalent in U. Lewin [9] showed that |a 2 | < 1.51 for every function f ∈ Σ given by (1.1). Posteriorly, Brannan and Clunie [3] improved Lewin's result and conjectured that |a 2 | ≤ √ 2 for every function f ∈ Σ given by (1.1). The coefficient estimate problem for each of the following Taylor Maclaurin coefficients:…”
Section: Introductionmentioning
confidence: 93%
“…Recently, many researchers have been exploring biunivalent functions associated with orthogonal polynomials, few to mention [22][23][24][25][26][27][28]. For Gegenbauer polynomial, as far as we know, there is little work associated with biunivalent functions in the literatures.…”
Section: Journal Of Function Spacesmentioning
confidence: 99%
“…Recently, Some several researcher such as ( for example [1], [2], [3], [4] [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [17], [21]) introduced new subclasses of bi-univalent functions and meromorphically bi-univalent functions and obtained estimates on the initial coefficients for functions in each of these subclasses.…”
Section: Introductionmentioning
confidence: 99%